Expression of leukemogenic recombinant viruses associated with a recessive gene in HRS/J mice (The Rockefeller University Press, 1980)
HRS/J inbred mice carry a mutant autosomal recessive gene (hr), which in homozygotes coincides with susceptibility to spontaneous thymic leukemia. Unlike their heterozygote (hr/+) littermates, hr/hr homozygotes express high levels of xenotropic virus during the preleukemic period, and viruses with a broadened host range (termed polytropic viruses) can be isolated from their preleukemic and leukemic tissues. Because hr/hr and hr/+ mice are otherwise genetically identical, the virological differences between them support the role of polytropic viruses in the generation of thymic leukemia. In the present report we show that the HRS/J polytropic viruses are env gene recombinants with unique oligonucleotide and peptide maps. These polytropic viruses appear to arise by recombination between ecotropic virus and an unidentified genome related, but not identical to, the endogenous xenotropic viruses. Moreover, polytropic viruses not only accelerate leukemogenesis in HRS/J mice, but also induce thymic leukemia in the low leukemia strain CBA/J. By contrast, cloned ecotropic and xenotropic viruses have no leukemogenic action.